PERSONAL FEATURES OF CHILDREN AND ADOLESCENTS ILL WITH RESPIRATORY TUBERCULOSIS EXPOSED AND NOT EXPOSED TO THE SOURCE OF INFECTION - N. V. Zolotova; A. A. Akhtyamova; V. V. Streltsov; G. V. Baranova; E. S. Ovsyankina; N. V. Yukhimenko (Туберкулез и болезни лёгких)
Specific personal features of 296 children and adolescents exposed to tuberculosis and those with unidentified exposure were comparatively analyzed. Children with unidentified exposure demonstrated psychic tension, poor self-control, poorly developed social communication skills which determined disruptive interpersonal relations and uneasy personal growth. Children exposed to tuberculosis in their families were characterized by judging didactive position towards their neighbors which was formed by dysfunctional patterns of relations in their parental families. Adolescent with unidentified exposure manifested the contrast combination of pre-morbid personal attitudes which had certain etiologic contribution to the development of borderline neurotic states. The higher level of destructive reactions in the interpersonal communication was observed in the adolescents exposed to tuberculosis in their families. Identified personal features are considered to be psychological factors determining the hyperactivation of adaptive systems at the pre-morbid state and consequent development of structural functional disorders in various systems of the host, as well as providing impact on the course of tuberculosis.